2017
DOI: 10.1371/journal.pone.0175583
|View full text |Cite
|
Sign up to set email alerts
|

The influence of journal submission guidelines on authors' reporting of statistics and use of open research practices

Abstract: From January 2014, Psychological Science introduced new submission guidelines that encouraged the use of effect sizes, estimation, and meta-analysis (the “new statistics”), required extra detail of methods, and offered badges for use of open science practices. We investigated the use of these practices in empirical articles published by Psychological Science and, for comparison, by the Journal of Experimental Psychology: General, during the period of January 2013 to December 2015. The use of null hypothesis si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
118
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(130 citation statements)
references
References 34 publications
11
118
0
1
Order By: Relevance
“…Previous research investigating the effectiveness of the badges in more detail found that after the introduction of the badges, data was more often available, correct, usable, and complete (Kidwell et al, 2016). These results are in line with the finding that journal submission guidelines in general can inspire desirable change in authors' behavior (Giofrè, Cumming, Fresc, Boedker, & Tressoldi, 2017; but see also Morris & Fritz, 2017). Note, however, that our design is observational, which does not allow us to draw a causal conclusion.…”
Section: Effectiveness Open Data Policysupporting
confidence: 82%
“…Previous research investigating the effectiveness of the badges in more detail found that after the introduction of the badges, data was more often available, correct, usable, and complete (Kidwell et al, 2016). These results are in line with the finding that journal submission guidelines in general can inspire desirable change in authors' behavior (Giofrè, Cumming, Fresc, Boedker, & Tressoldi, 2017; but see also Morris & Fritz, 2017). Note, however, that our design is observational, which does not allow us to draw a causal conclusion.…”
Section: Effectiveness Open Data Policysupporting
confidence: 82%
“…Previous research investigating the effectiveness of the badges in more detail found that after the introduction of the badges, data was more often available, correct, usable, and complete (Kidwell et al, 2016). These results are in line with the finding that journal submission guidelines in general can inspire desirable change in authors' behavior (Giofrè, Cumming, Fresc, Boedker, & Tressoldi, 2017; but see also Morris & Fritz, 2017).…”
Section: Effectiveness Open Data Policysupporting
confidence: 78%
“…(Giofrè et al, 2017;Kidwell et al, 2016). Even though these results seem promising, they should be interpreted with care.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Trofimovich and Ellis (2015) adopted the Open Science Badges for Language Learning, and several other journals now also value open materials and data in this way (e.g., "Author guidelines for contributors," 2017; "Instructions for contributors," 2017). Kidwell et al (2016) and Giofrè, Cumming, Fresc, Boedker, and Tressoldi (2017) have provided quantitative evidence for the effectiveness of this initiative for the transparency of materials and data. Indeed, partly as a result of these initiatives and push from journal editors, IRIS now holds 24 sets of L2 data, in addition to approximately 3,600 files of materials and analysis protocols.…”
Section: Recommendationmentioning
confidence: 99%